Efficacy against footrot of a Bacteroides nodosus 265 (serogroup H) pilus vaccine expressed in Pseudomonas aeruginosa. - Elleman, T C (1988)
Pili of Bacteroides nodosus 265 (serogroup H) were expressed in Pseudomonas aeruginosa both alone and in combination with pili from B. nodosus 198 (serogroup A). Pilin genes from B. nodosus were introduced on plasmid-borne, thermoregulated expression systems, either singly or as tandem genes from two separate strains in a single transcription unit. Despite the absence of a posttranslational cleavage of pilin which occurs in B. nodosus, pili prepared from P. aeruginosa harboring the pilin gene of B. nodosus 265 protected sheep against footrot after challenge by B. nodosus 265. Organisms harboring pilin genes from the two different serogroups of B. nodosus produced serologically distinct populations of pili on each cell, and pili from these cells protected sheep against footrot after challenges with B. nodosus strains 198 and 265.